2018
DOI: 10.1007/s11553-018-0678-6
|View full text |Cite
|
Sign up to set email alerts
|

Apps zur Förderung von körperlicher Aktivität

Abstract: International wurden Einstellungen von Erwachsenen ab 50 Jahren bezüglich einer Nutzung von evidenzinformierten Apps zur Bewegungsförderung bereits unter verschiedenen Aspekten untersucht. In Deutschland ist bisher wenig zu Einstellungen bezüglich solcher Apps in dieser Population bekannt. Ziele der Arbeit: Ziel der Fokusgruppeninterviews war es, Einblicke zu Einstellungen, Akzeptanz und Nutzungspräferenzen von Smartphone-Applikationen (Apps) zur Bewegungsförderung in der Altersgruppe ≥50 Jahre zu erhalten. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Facing the surge of non-communicable diseases (NCD) (2), health promotion strategies that aim to empower people to increase control over their health behavior (behavioral prevention), e.g., by strengthening health literacy to reduce NCD risk factors, are seen as one pivotal approach toward healthy aging. In recent years, the rapid development and increased use of digital health technologies, such as wearables, dietary tools, and health and physical activity smartphone applications, have become highly relevant for health promotion (3)(4)(5). In addition to wearable technologies, ambient sensors have been used to analyze and promote activity-related indicators (6).…”
Section: Introductionmentioning
confidence: 99%
“…Facing the surge of non-communicable diseases (NCD) (2), health promotion strategies that aim to empower people to increase control over their health behavior (behavioral prevention), e.g., by strengthening health literacy to reduce NCD risk factors, are seen as one pivotal approach toward healthy aging. In recent years, the rapid development and increased use of digital health technologies, such as wearables, dietary tools, and health and physical activity smartphone applications, have become highly relevant for health promotion (3)(4)(5). In addition to wearable technologies, ambient sensors have been used to analyze and promote activity-related indicators (6).…”
Section: Introductionmentioning
confidence: 99%
“…Wichmann et al [ 54 ] criticized, despite all the potential benefits, the general academic enthusiasm about introducing DIGAs into the health care system, even though there is little empirical evidence about their long-term effectivity, or the usage over several years. Urban [ 55 ] conducted qualitative interviews to research the user perception of elderly people.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, preferences for apps addressing physical activity could also depend on other factors such as age. For example, a focus group study in Germany showed that older adults prefer to use simple-to-use fitness apps with few features, automated tracking of data, and active feedback to reach their goals [ 19 ]. A repetition of the present survey could be used to quantitatively investigate the influence of the COVID-19 pandemic and other factors on the use of digital technologies for physical activity promotion.…”
Section: Discussionmentioning
confidence: 99%